On Galerkin's method for evolutionary equations with pulse influence - Ilolov, M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A new modification of Galerkin's approximation scheme is proposed for evolutionary equations with pulse influence and its convergence is proved. The result obtained is extended to the pulse evolutionary equations with deviating argument.